Anti-Hypertensive Herbs and Their Mechanisms of Action: Part II - Anwar, M. Akhtar; Al Disi, Sara S.; Eid, Ali H. (Frontiers in Pharmacology, 2016)
Traditional medicine has a history extending back to thousands of years, and during the intervening time, man has identified the healing properties of a very broad range of plants. Globally, the use of herbal therapies to treat and manage cardiovascular disease (CVD) is on the rise. This is the second part of our comprehensive review where we discuss the mechanisms of plants and herbs used for the treatment and management of high blood pressure. Similar to the first part, PubMed and ScienceDirect databases were utilized, and the following keywords and phrases were used as inclusion criteria: hypertension, high blood pressure, herbal medicine, complementary and alternative medicine, endothelial cells, nitric oxide (NO), vascular smooth muscle cell (VSMC) proliferation, hydrogen sulfide, nuclear factor kappa-B (NF-κB), oxidative stress, and epigenetics/epigenomics. Each of the aforementioned keywords was co-joined with plant or herb in question, and where possible with its constituent molecule(s). This part deals in particular with plants that are used, albeit less frequently, for the treatment and management of hypertension. We then discuss the interplay between herbs/prescription drugs and herbs/epigenetics in the context of this disease. The review then concludes with a recommendation for more rigorous, well-developed clinical trials to concretely determine the beneficial impact of herbs and plants on hypertension and a disease-free living.